Epstein–Barr virus and its association with Fascin expression in colorectal cancers in the Syrian population: A tissue microarray study. Issue 7 (3rd July 2017) - Al-Antary, Noor; Farghaly, Hanan; Aboulkassim, Tahar; Yasmeen, Amber; Akil, Nizar; Al Moustafa, Ala-Eddin
ABSTRACT: Colorectal cancer (CRC) is the third most common malignancy in both men and women worldwide. Colorectal carcinogenesis is a complex, multistep process involving environmental and lifestyle features as well as sequential genetic changes in addition to bacterial and viral infections. Viral infection has a proven role in the incidence of approximately 20% of human cancers including gastric malignancies. Accordingly, Epstein–Barr virus (EBV) has been recently shown to be present in human gastric cancers, which could play an important role in the initiation and progression of these cancers. Therefore, this work explores the prevalence of EBV in 102 CRC tissues from the Syrian population using polymerase chain reaction (PCR) and tissue microarray (TMA) analysis. We found that EBV is present in 37 (36.27%) of CRC samples. Additionally, the expression of LMP1 onco-protein of EBV was found to be correlated with Fascin expression/overexpression in the majority of CRC tissue samples, which are intermediate/high grade invasive carcinomas. Our data indicate that EBV is present in CRC and its presence is associated with more aggressive cancer phenotype. Consequently, future investigations are needed to expose the role of EBV in CRC initiation and progression.